Protein Phosphatase 2A Activation Via ApoER2 in Trophoblasts Drives Preeclampsia in a Mouse Model of the Antiphospholipid Syndrome. Issue 7 (16th August 2021) - Chu, Haiyan; Sacharidou, Anastasia; Nguyen, An; Li, Chun; Chambliss, Ken L.; Salmon, Jane E.; Shen, Yu-Min; Lo, Julie; Leone, Gustavo W.; Herz, Joachim; Hui, David Y.; Marciano, Denise K.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Rationale: Preeclampsia is a potentially life-threatening, placenta-based hypertensive disorder during pregnancy, and the antiphospholipid syndrome (APS) frequently leads to preeclampsia. APS pregnancies are also complicated by fetal demise and intrauterine growth restriction. Objective: Here, we determined how the circulating antiphospholipid antibodies (aPL) characteristic of APS alter placental trophoblast function to cause preeclampsia and also endanger the fetus. Methods and Results: Experiments were performed in mice, in cultured human trophoblasts, and in human placenta samples. Effects of aPL and IgG from healthy subjects were compared. Based on prior findings in culture, in vivo studies were done in mice deficient in ApoER2 (apolipoprotein E receptor 2) in trophoblasts. End points in tissues and cells were determined by enzymatic assay, quantitative polymerase chain reaction, ELISA, or immunoblotting. Whereas in wild-type mice aPL caused maternal hypertension and proteinuria, fetal demise and intrauterine growth restriction, mice lacking trophoblast ApoER2 were protected. In culture, aPL attenuated trophoblast proliferation and migration via an ApoER2-related protein complex comprised of the PP2A (protein phosphatase 2A), Dab2 (disabled-2), and JIP4 (Jun-N-terminal kinase-interacting protein 4). Via trophoblast ApoER2 in mice and in culture, aPL-stimulated PP2A activity, leading to MMP14 (matrix metallopeptidase 14) and HIF1α (hypoxia-inducible factor 1) upregulation and increased soluble endoglin production. HIF1α and soluble endoglin upregulation was related to PP2A desphosphorylation of PHD2 (prolyl hydroxylase domain containing protein 2). In mice PP2A inhibition prevented aPL-induced maternal hypertension and proteinuria, and fetal demise and intrauterine growth restriction. Placentas from patients with APS displayed PP2A hyperactivation, PHD2 dephosphorylation and HIF1α upregulation, and these findings were generalizable to placentas of women with preeclampsia from causes other from APS. Conclusions: In APS, pregnancies trophoblasts are the critical cell target of aPL, and via ApoER2-dependent PP2A activation, aPL cause preeclampsia through MMP14 upregulation and PHD2 dephosphorylation leading to HIF1α and soluble endoglin upregulation. Moreover, parallel processes may be operative in preeclampsia in non-APS patients. Interventions targeting PP2A may provide novel means to combat APS-related preeclampsia and preeclampsia unrelated to APS.